Cauchy's interlace theorem and lower bounds for the spectral radius. (15th April 2000) - Mercer, A. McD.; Mercer, Peter R.
Abstract : We present a short and simple proof of the well-known Cauchy interlace theorem. We use the theorem to improve some lower bound estimates for the spectral radius of a real symmetric matrix.